Effectiveness of the Implementation of Communication in Ship Operational Activities - Noferman Gea; Muhammad A Naim (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Communication is very important for the company's operational needs during maintenance activities, preventing ship accidents, loading/unloading, and guard duty. The use of communication aims to reduce the risk or failure of transportation activities and have an impact on the quality of customer cargo services, this is done routinely and ensures that the communication is carried out in accordance with shipping safety standards. This research uses a theoretical and practical approach sourced from previous research, namely journals and the results of findings during work, so that the research concludes that communication effectiveness can be produced by all components on board the ship with different backgrounds, with the aim that the results of crew communication can provide better performance on ship activities and productivity